Regional Government Cooperation with Business Entities for Efficiency in the Public Street Lighting Sector for the Potential to Increase Purwakarta Regency's Original Regional Income - Abdurachman, Iman; Rizal, Muhammad; Dai, Ratna Meisa (International Journal of Science and Society, 2024)
This research aims to analyze the implementation of Regional Government Cooperation with Business Entities (KPBU) in the Public Street Lighting (PJU) sector in Purwakarta district. The method used in this research is a qualitative method with a descriptive approach with secondary data from books and other sources that support the discussion of this research, as well as media and internet documents, included in the data category. This research shows that if government collaboration with PPP is successful, several things must be considered. Relationships, resources, networks, organizations. In other words, this collaboration is strategically important for both parties. parties and must complement each other, information from both parties must be considered and maintained. Mutual trust is important, especially the efficiency of PJU costs/budgets in the APBD. The implementation of the PPP policy is included in the category of complex cooperation because the mechanism for payment of services is based on payment from savings, the Government does not bear the initial costs (no investment) and does not bear the risk of state losses (zero risk). PPP scheme PJU business entities with unsolicited projects have so far not found any potential complaints or indications of state financial losses because so far they have still complied with the precautionary principle.